Students' creative thinking skills on the circle subject in terms of learning obstacle and learning trajectory - Diana, N; Suryadi, D; Dahlan (Journal of physics. Conference series, 2020)
The study aims to describe students' creative thinking skills in circle material based on students' learning obstacle and trajectory. This research applied descriptive qualitative. The instruments used were circular questions and interviews. Data analysis carried out along with the data taken by analyzing students' creative thinking skills based on students' learning obstacle and trajectory. The research subjects were VI semester students who were able to handle analytical geometry. The results of the study shown that, most students experience learning obstacle (1). Students have difficulties in finding concepts from the meaning of circles, (2). Students have difficulties working on material circle questions and without re-examining the answers (3). Students found out difficulties in a concept from the general formula of the equation of the circle and make the graph, (4). Learning materials presented in textbooks do not build students' creative thinking skills, so they do not support meaningful learning. Learning trajectory based on analysis of learning obstacle experienced by students and analysis of causes of difficulties can occur. Preparation of hypothetical learning trajectory through learning situations designed is expected to create students' creative thinking, indeed, the student reconstruction process is created independent students form the concept of the formula set.